Do I decide my career? Linking career stress, career exploration, and future work self to career planning or indecision - Zhang, Zemei; Yu, Xuan; Liu, Xuhong (Frontiers in Psychology, 2022)
Career planning and career decision are important tasks for college students. The process may be affected by career stress, career exploration, and future work self, with some students facing career indecision. Combining both construction career and proactive motivation model, this study investigated the relationships between career stress, career exploration, future work self, career planning and career indecision among 1012 Chinese college students using the Structure equation model (SEM) to test the proposed mediation model. Results show that career stress negatively predicts career planning, while career exploration positively predicts career planning.The mediating role of future work self has on career stress and career exploration’s effects on both career planning and career indecision was verified. Moreover, the study also found future work self’s positive effects on both career planning and career indecision in Chinese college students. Finally, the study’s theoretical and practical significance and implications are discussed.